Changing Paradigms in Library Education: From Library Science to Information Science to Knowledge Science (Eastern Librarian, 2012)
The main objective of this paper is to explore the changes in library education in the context of the emergence of both information science and knowledge management. This paper is based on the review of scientific literature published in books, journals, websites, and other secondary sources and on the authors own viewpoints. The review discusses library sciences encounter with information science, and shows the changes in the paradigm of library science from library-orientation to information focus. In the context of renaming the discipline of library science as library and information science (LIS), this paper explores the curricular trends and the changes in the professional practice of librarianship. The discipline of LIS is now encountering with the emergence of knowledge management (KM), and is moving towards knowledge paradigm. The review also identifies some factors that influenced the change in library education and practice. The paper concludes with the prediction of a new discipline of knowledge science suggesting the renaming of library and information science as library and knowledge science. DOI: http://dx.doi.org/10.3329/el.v23i1.12115 Eastern Librarian Vol.23(1) 2012 pp.1-23